The effect of anionic dispersants on grindability of different rank coals - Atesok, G.; Ozer, M.; Boylu, F.; Dıncer, H. (Elsevier BV, 2005)
Abstract The effect of PSS (Sodium Polystyrene Sulphonate) and NSF (Naphthalene Sulphonate Formaldehyde Condensate) chemicals used to control the pulp rheology on the grindability of coals was studied. Zonguldak region bituminous coal and Istanbul region brown coal samples that high and low rank were used. Wet grinding tests with two coal samples were performed with or without PSS and NSF under constant grinding conditions: solid ratios ranged from 50% to 60% with 0–60 min grinding periods. In the present study, grinding conditions of coal with high pulp solid ratio were improved through the lowering of the viscosity of the coal by using the dispersing agents, PSS and NSF, during the grinding stage and evaluation were made by using the “efficiency factor”. It is possible to increase the amount of finely ground bituminous coal from Zonguldak by 20% and 16%, if optimum concentrations of PSS (0.3%) and NSF (0.7%) are used, respectively. Whereas, the increase in the case of finely ground lignite from Istanbul was 32% and 20%, respectively.